Leisure mobility and individuals’ relationship to the living environment: a comparison between the Paris and Rome urban regions. - Nessi, Hélène (Environnement urbain)

(untitled) (Institut National de Recherche Scientifique Centre Urbanisation Culture et Société, 2017)
In this article we examine how (alongside with other factors) the relationship that individuals have to their living environment affects their leisure mobility. We first elaborate a typology (comprising 5 types) of individuals according to their stated relationship to their living environment. Using a statistical approach, we then show that this typology partially explains inter-individual differences in leisure mobility, after taking into account other socioeconomic and spatial explanatory factors: income, level of education, profession, residential location (esp. density of residential area) and demographic characteristics. This statistical argument is complemented with a qualitative study of the meanings given by individuals to their living environments and leisure mobility practices, which ultimately contributes to better understand the drivers of leisure mobility and to emphasize in particular the notion of compensatory mobility. A given urban context may accomodate very different practices and very diverse life projects and the approach developed in the paper has allowed to move away from deterministic explanations for leisure mobility.